Rapid adaptation of multisensory integration in vestibular pathways - Carriot, Jerome; Jamali, Mohsen; Cullen, Kathleen E. (Frontiers in Systems Neuroscience, 2015)
Sensing gravity is vital for our perception of spatial orientation, the control of upright posture, and generation of our every day activities. When an astronaut transitions to microgravity or returns to earth, the vestibular input arising from self-motion will not match the brain’s expectation. Our recent neurophysiological studies have provided insight into how the nervous system rapidly reorganizes when vestibular input becomes unreliable by both 1) updating its internal model of the sensory consequences of motion and 2) up-weighting more reliable extra-vestibular information. These neural strategies, in turn, are linked to improvements in sensorimotor performance (e.g., gaze and postural stability, locomotion, orienting) and perception characterized by similar time courses. We suggest that furthering our understanding of the neural mechanisms that underlie sensorimotor adaptation will have important implications for optimizing training programs for astronauts before and after space exploration missions and for the design of goal-oriented rehabilitation for patients.